SELF AND PEER-CORRECTION TECHNIQUES IN TEACHING WRITING - Atika Salman Paris; Mul Muliadi; Baiq Santika Lestari (LPPM Institut Pendidikan Nusantara Global, 2022)
This quantitative study aimed at finding out the effectiveness of self and peer-correction techniques in teaching writing at the twelfth graders of MAS Muallimin NW Boro Tumbuh in the academic year 2022/2023. The samples of this study were taken through random sampling technique consisting of 25 students. The data were collected from pre-test and post-test. The gained data were analyzed using descriptive statistics and paired sample t-test. This test was administrated to know answer the hypothesis. The result of the study indicated that self and peer-correction technique was significantly effective in teaching writing for the twelfth graders of MAS Muallimin NW Boro Tumbuh in the academic year 2022/2023. This can be seen from the result of the students’ mean score in the pre-test and post-test. In the pre-test, the mean score was 8.07 with the standard deviation 1.809. In the post-test, whereas, the mean score was 9.77 and the standard deviation was 2.221. The result proved that the pre-test was lower than the post-test. In addition, the hypothesis testing showed that the alternative hypothesis was accepted. In a nutshell, the self and peer—correction technique is an advisable technique to apply by the English teacher in their writing class.